2018
DOI: 10.1016/j.neuroscience.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ca2+ and BK Channels of Locus Coeruleus (LC) Neurons as a Brake to the CO2 Chemosensitivity Response of Rats

Abstract: The cellular mechanisms by which LC neurons respond to hypercapnia are usually attributed to an "accelerator" whereby hypercapnic acidosis causes an inhibition of K channels or activation of Na and Ca channels to depolarize CO-sensitive neurons. Nevertheless, it is still unknown if this "accelerator" mechanism could be controlled by a brake phenomenon. Whole-cell patch clamping, fluorescence imaging microscopy and plethysmography were used to study the chemosensitive response of the LC neurons. Hypercapnic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Several studies demonstrated that hypercapnia stimulates LC and C1 group neurons and has an excitatory effect on brainstem respiratory neurons (Viemari, 2008;Gargaglioni et al, 2010;Magalhães et al, 2018). These neurons express several chemosensitive K + channels (Gargaglioni et al, 2010, and references therein), among which the pH-sensitive Kir channels (D'Adamo et al, 2011), the leak-conductance two-pore domain TASK-1 channels (Bayliss et al, 2001), the large conductance Ca 2+ -activated K + (BK) channels (Imber et al, 2018), the Kv channels and the acid-sensing ion channel (ASICs). The presence of multiple pH-sensitive ion channels, which may have different sensitivity to pH variation, can result in a fine modulation of neuronal response to hypercapnia, by means of a mechanism mainly based on inhibition of K + channels.…”
Section: Other Pharmacological Targetsmentioning
confidence: 99%
“…Several studies demonstrated that hypercapnia stimulates LC and C1 group neurons and has an excitatory effect on brainstem respiratory neurons (Viemari, 2008;Gargaglioni et al, 2010;Magalhães et al, 2018). These neurons express several chemosensitive K + channels (Gargaglioni et al, 2010, and references therein), among which the pH-sensitive Kir channels (D'Adamo et al, 2011), the leak-conductance two-pore domain TASK-1 channels (Bayliss et al, 2001), the large conductance Ca 2+ -activated K + (BK) channels (Imber et al, 2018), the Kv channels and the acid-sensing ion channel (ASICs). The presence of multiple pH-sensitive ion channels, which may have different sensitivity to pH variation, can result in a fine modulation of neuronal response to hypercapnia, by means of a mechanism mainly based on inhibition of K + channels.…”
Section: Other Pharmacological Targetsmentioning
confidence: 99%
“…However, GluA2‐lacking, and thus calcium‐permeable, AMPA receptors have been detected in many brain regions (Ogoshi & Weiss, 2003 ; Toth & McBain, 1998 ). Calcium currents, via L‐type and BK calcium channels, have been shown to contribute to the intrinsic pacemaking properties of LC noradrenergic neurons (Aghajanian et al, 1983 ; de Oliveira et al, 2010 , 2019 ; Imber et al, 2018 ; Matschke et al, 2018 ). These spontaneous action potentials also seem to trigger Ca 2+ ‐induced mitochondrial oxidative stress, which may underlie the vulnerability of LC neurons to ageing and stress, particularly in neurodegenerative disorders such as Alzheimer's disease and Parkinson's disease (Sanchez‐Padilla et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…(F) Injection of BK inhibitor paxilline directly into the LC to remove the oscillatory brake does not affect baseline respiration but augments the HCVR. Panel adapted from (Imber et al, 2018), Figure 9B.…”
Section: Criteria 4 Andmentioning
confidence: 99%
“…The expression of K ir 4.1/K ir 5.1 in both LC neurons and astrocytes, where they are also implicated as potential pH sensors, confounds interpretation of physiological experiments performed in whole animal K ir 5.1 knockouts and further supports a move to cell type specific manipulations moving forward. The L-type calcium channels that contribute to subthreshold oscillations and action potential firing are not directly affected by internal pH and LC neurons still depolarize in response to CO 2 when oscillations are blocked with nifedipine (Figure 7E) (Filosa and Putnam, 2003;Imber and Putnam, 2012;Li and Putnam, 2013;Imber et al, 2014;Imber et al, 2018;Li et al, 2021). However, the subthreshold oscillations are modulated by cAMP/PKA signaling and can be indirectly facilitated by CO 2 -dependent intracellular acidification, uptake of bicarbonate and activation of a bicarbonatesensitive soluble adenylate cyclase (sAC) (Imber et al, 2014).…”
Section: Criteria 4 Andmentioning
confidence: 99%
See 1 more Smart Citation